PERANCANGAN SIGN SYSTEM OBJEK WISATA DANAU KEMBAR - Yoli Efrina, Dr. Budiwirman, M.Pd, Hendra Afriwan, S.Sn, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of this (1) research is to design The Twins Lake signed system, this research will discuss the signing system designed for The Twins Lake tourism object. (2) The sign designed are attractive, simple, colors determined, typography,and communicative layouts to represent distinctive feature local community. The Source of this research using collecting data field method, include observation, interview and also through documentation on tourism in The Twins Lake. The result of this research is communicative sign system for the Twins Lake visitors, within information about tourism object of The Twins Lake in the picture, colors typography, and attractive layouts.